Predictors of sustained physical activity: behaviour, bodily health, and the living environment - Diaconașu, Delia Elena; Stoleriu, Iulian; Câmpanu, Ioana Andreea; Andrei, Ana-Maria; Boncu, Ștefan; Honceriu, Cezar; Mocanu, Veronica; Juravle, Georgiana (Frontiers in Physiology, 2024)
This study examined the determinants of sustained physical activity. Eighty-four participants undertook a seven-weeks walking regime (i.e., a one-hour biometrically-monitored walk, at least five days/week), with bioelectrical impedance (BIA) and total cholesterol capillary blood measurements performed before and after programme. To investigate behavioural habit formation, seven weeks after walking termination, all participants were interviewed and (health) re-tested. Data were modelled with an artificial neural network (ANN) cascading algorithm. Our results highlight the successful prediction of continued physical activity by considering one's physical fitness state, the environmental living context, and risk for cardiovascular disease. Importantly, those ANN models also taking body mass index (BMI) and blood cholesterol as predictors excel at predicting walking continuation (i.e., predictions with 93% predictability). These results are first to highlight the type and importance of available physiological drivers in maintaining a sustained physical activity regime such as walking. They are discussed within the framework of habit formation and the nowadays health and/or well-being focus.